PVDF plasticizer for electrode fabrication, and universal battery application thereof
The use of a plasticized PVDF binder with tetraglyme, diglyme, or triglyme in electrode slurry addresses conductivity and ion diffusion issues, enhancing battery performance through improved rate capability and cyclability.
Patent Information
- Application Number
- JP2024089985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2024-06-03
- Publication Date
- 2024-12-19
AI Technical Summary
Existing PVDF binders in electrode manufacturing for batteries face challenges in enhancing conductivity and ion diffusion, leading to reduced rate performance and cyclability, and conventional plasticizers do not significantly improve electrochemical performance.
A plasticized PVDF binder comprising tetraglyme, diglyme, or triglyme is used in the electrode slurry, along with electrode active materials and conductive carbon, to improve conductivity and ion transfer.
The plasticized PVDF binder enhances electrode performance by improving rate capability and cyclability, facilitating easier manufacturing and maintaining electrochemical stability.
Smart Images

Figure 2024177100000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a plasticizer for polyvinylidene fluoride (PVDF) used as a binder for the manufacture of electrodes. [Background technology]
[0002] Typically, in secondary batteries for electrochemical energy conversion and storage, two electrodes and an electrolyte are commonly used, with electrochemical reactions taking place at both electrodes, leading to more or less significant changes in the composition of the electrolyte. During electrochemical processes in the cell, components of the electrolyte solution are often consumed or new ones are generated. Related changes in the electrolyte properties are in most cases unwelcome, as they can lead, for example, to a decrease in ionic conductivity or an increase in the internal resistance of the device. A certain minimum amount of electrolyte is essential for the sustained performance of the cell.
[0003] Representative examples of metal-ion batteries reported in various studies include sodium, lithium, potassium, magnesium, calcium, and fluorine-ion batteries. Generally, in any battery, the electrode material is a key factor that affects the battery performance and cost compared to other materials. Although several studies have been focused on material discovery, notable progress has also been made in engineering. The motivation to improve the electrode performance is mainly from the electrochemical storage properties of the active materials. Nevertheless, the fabrication of the electrode plays a major role that significantly affects the battery performance. In particular, the binder, conductive carbon, solvent, and their ratios also play a significant role in determining the rate capability, cycle performance, and energy density.
[0004] The manufacturing procedure for electrodes is roughly as follows: the battery constituents, including the electrode active material, conductive carbon, and binder, are homogenized in a solvent. The resulting suspension is called the electrode slurry, which is then coated on a metal foil, e.g., Al and / or Cu, to obtain an electrode. Several studies have been conducted focusing on the different components of the battery, such as the electrode, electrolyte, separator, and binder.
[0005] The main purpose of the binder is to hold the active material together in the electrode and improve the adhesion between the electrode and the current collector. The addition of the binder to the active material requires careful consideration. The quality measurements considered to select the appropriate binder are adhesive strength, hydrophilicity, thermal and electrochemical stability to withstand long charge-discharge cycles, and non-toxicity. In addition, the crystallite size, electrical conductivity, and ion diffusion ability of the binder are important consideration parameters as well. The list of binders includes both natural and synthetic materials. Polyvinylidene fluoride (PVDF) is a semi-crystalline polymer that is widely used in the manufacture of electrochemical devices such as Li-ion batteries, supercapacitors, and nanogenerators due to its excellent properties such as mechanical, thermal, and chemical stability, and non-toxicity. A huge number of literature has been reported on the binding efficiency of PVDF. From this, PVDF was found to be a suitable binder for almost all types of electrode materials, including activated carbon, carbon nanofibers, graphene, carbon nanotubes, and conductive polymers (polyaniline, polythiophene, polypyrrole, and metal oxides). Several publications that discuss PVDF as a suitable binder are summarized below.
[0006] KR101413433B1 relates to a binder material for secondary batteries. The disclosed material includes rosin and rosin derivatives. In addition, the material may further include a fluorine-containing polymer. The fluorine-containing polymer includes PVDF and other copolymers such as PVDF-hexafluoropropylene, PVDF-tetrafluoroethylene, etc.
[0007] WO2016123168A1 discloses a lithium ion capacitor. The capacitor includes an anode including a conductive support, a first mixture including coconut shell flour-derived carbon, conductive carbon black, and a PVDF binder coated on the conductive support. A second mixture including micron-sized lithium metal particles having an encapsulating shell is coated on the first mixture. The encapsulating shell is LiPF6 , mineral oil, and a thermoplastic binder.
[0008] WO2018084431A1 relates to an electrode for a secondary battery capable of preventing a short circuit phenomenon of the electrode. The electrode comprises an active material layer on a current collector, the layer including a binder including PVDF. A short circuit prevention layer is formed on the active material layer, and the prevention layer includes a porous polymer fiber web formed by accumulating fibers of a heat-resistant polymer material.
[0009] WO2019074025A1 relates to a method for producing an electrode for a non-aqueous electrolyte secondary battery. The method includes mixing an electrode active material, a PVDF binder, a first solvent, and a second solvent to prepare a dispersion. The second solvent is then removed from the dispersion to prepare a slurry, and the slurry is then applied onto a current collector.
[0010] There are several other state-of-the-art documents that discuss PVDF as a preferred binder material for metal-ion battery electrode fabrication. Although PVDF has been widely used and studied as a binder material for batteries, there are some challenges associated with it. For example, PVDF is considered to be unsuitable for enhancing electrical conductivity and ion diffusion, which leads to a significant decrease in rate capability and cyclability in the long term. In addition, carbonate-based organic solvents, phthalates, and organic acetates are used as state-of-the-art plasticizers. However, the electrochemical performance has not been significantly improved. A suitable plasticizer for PVDF is required to control the crystallite size of long chains, which enhances electrical conductivity and allows the metal ions (Li) to flow in and out of the electrode while leaving the particles intact. + , Na + , K + This is not observed in the state of the art where plasticizers are added directly during the slurry preparation without modifying the conventional manufacturing process, so the resulting electrodes are of little value from a commercial point of view.
[0011] Considering the above, plasticizing the PVDF binder is a promising option to ensure overcoming one or more of the aforementioned challenges. Once plasticized, the PVDF polymer particles become soft, flowable, and can adhere to the powdered materials during fabrication, resulting in an irreversible and highly connected electrode. Considering the same, there is a long-standing need for electrode slurries, which can provide an easy fabrication technique and improve the electrochemical properties of the electrodes.
[0012] It was therefore an object of the present invention to provide an electrode slurry that is effective in alleviating one or more of the problems in the prior art. Summary of the Invention
[0013] Surprisingly, it has been found that the above objectives are achieved by providing an electrode slurry as described below.
[0014] Thus, in one aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: 60% to 98% by weight of an electrode active material; 0% to 20% by weight of conductive carbon, and 1% to 20% by weight of plasticizing binder For electrode slurries comprising: The plasticized binder is characterized in that it comprises polyvinylidene fluoride and a plasticizer selected from the group consisting of tetraglyme, diglyme, triglyme, and monoglyme.
[0015] In one embodiment, the plasticizer is present in an amount ranging from 1% to 50% by weight based on the weight of polyvinylidene fluoride.
[0016] In another embodiment, the plasticized binder is obtained by mixing polyvinylidene fluoride with a plasticizer.
[0017] In another aspect, the present invention relates to a method for preparing said electrode slurry by mixing an electrode active material, a conductive carbon, and a plasticizing binder in the presence of a solvent.
[0018] In one embodiment, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylsulfoxide (DMSO), and dimethylacetamide (DMAc).
[0019] In yet another aspect, the present invention relates to a method for preparing an electrode by applying the above-described electrode slurry onto a current collector.
[0020] In one embodiment, the current collector is dried at a temperature ranging from 50°C to 200°C.
[0021] In yet another aspect, the present invention relates to an electrode resulting from the above process.
[0022] In a further aspect, the present invention relates to a battery comprising the above electrode.
[0023] In one embodiment, the battery is selected from a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery, an aluminum ion battery, a calcium ion battery, a fluorine ion battery, an aqueous battery, and a primary battery.
[0024] In another aspect, the present invention relates to an electrolytic device comprising the above-described electrode.
[0025] In yet another aspect, the invention relates to a fuel cell comprising the above-described electrode. [Brief description of the drawings]
[0026] 1(a)-(b) show the constant current charge / discharge profile and rate capability of a lithium iron phosphate cathode for a lithium ion battery according to one embodiment of the present invention.
[0027] 2(a)-(b) show the galvanostatic charge-discharge profile, rate capability, and cycle capability of a graphite anode for a lithium ion battery according to one embodiment of the present invention.
[0028] 3(a)-(c) show the galvanostatic charge-discharge profile, rate capability, and cycle capability of a lithium nickel manganese cobalt oxide cathode for a lithium ion battery according to one embodiment of the present invention.
[0029] 4(a)-(d) show the galvanostatic charge-discharge profile, rate capability (using tetraglyme and diglyme as plasticizers), and cycle capability (using tetraglyme as plasticizer) of a hard carbon anode for a sodium-ion battery according to one embodiment of the present invention.
[0030] 5(a) to (c) show a sodium ion battery Na 3 (VO) 2 (PO 4 ) 2 Figure 2 shows the galvanostatic charge-discharge profile, rate capability, and cycle capability of the F cathode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Before describing the present invention, it is to be understood that the terms used herein are not limiting, as the scope of the invention as presently claimed is limited only by the appended claims.
[0032] As used herein, the terms "comprising", "comprises" and "consisting of" are synonymous with "including", "including" or "comprising", "including" and are not inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps. As used herein, the terms "comprising", "comprising" and "consisting of" will be understood to include the terms "consisting of", "consisting of" and "consisting of".
[0033] Furthermore, terms such as "first," "second," "third," or "(a)," "(b)," "(c)," "(d)" in the description and claims are used to distinguish between similar elements and do not necessarily describe a sequential or chronological order. It is understood that the terms so used are interchangeable under appropriate circumstances, and that the embodiments of the invention described herein can operate in sequences other than as described or illustrated herein. When terms such as "first," "second," "third," or "(A)," "(B)" and "(C)" or "(a)," "(b)," "(c)," "(d)," "I," "ii," etc., relate to steps of a method, use, or assay, there is no consistency of time or time interval between the steps, i.e., the steps may be performed simultaneously or there may be intervals of seconds, minutes, hours, days, weeks, months, or years between the steps, unless otherwise specified in the application as described above or below.
[0034] In the following text, the various aspects of the invention are defined in more detail. Each aspect thus defined can be combined with any other aspect, unless expressly indicated to the contrary. In particular, any feature indicated as being preferred or advantageous can be combined with any other feature indicated as being preferred or advantageous.
[0035] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the presently claimed invention. Thus, the appearances of the phrase "in one embodiment" or "in an embodiment" in various places throughout this specification do not necessarily all refer to the same embodiment, although they may. Furthermore, particular features, structures, or characteristics can be combined in any suitable manner in one or more embodiments, as would be apparent to one of ordinary skill in the art from this disclosure. Furthermore, while some embodiments described herein include some features and do not include other features included in other embodiments, combinations of features from different embodiments are intended to form different embodiments within the scope of the present invention and as would be understood by one of ordinary skill in the art. For example, in the appended claims, any of the claimed embodiments can be used in any combination.
[0036] Furthermore, ranges defined throughout the specification are inclusive, i.e., a range of 1 to 10 means that both 1 and 10 are included within the range. For the avoidance of doubt, applicants have equivalent rights pursuant to applicable law.
[0037] As used herein, the terms "charging" and "charging" may refer to the process of supplying electrochemical energy to a cell.
[0038] As used herein, the terms "discharging" and "discharging" refer to the process of removing electrochemical energy from a cell, for example, when the cell is used to perform a desired task.
[0039] As used herein, the term "positive electrode" may refer to the electrode (often called the cathode) where electrochemical reduction occurs during the discharging process.
[0040] As used herein, the term "negative electrode" may refer to the electrode (often called the anode) where electrochemical oxidation occurs during the discharging process.
[0041] One aspect of the present invention relates to an electrode slurry.
[0042] In one embodiment, the electrode slurry comprises (a) 60% to 98% by weight of electrode active material, (b) 0% to 20% by weight of conductive carbon, and (c) 1% to 20% by weight of a plasticizing binder, where the weight percentages are based on the total weight of the slurry.
[0043] The selection of a suitable electrode active material depends on the type of battery and electrode, i.e., positive or negative. In one embodiment, active materials capable of inserting and deintercalating metal ions are used, which can be broadly divided into a group of inorganic compounds and a group of organic compounds.
[0044] Examples of the electrode active material in the inorganic compound group include transition metal oxides, transition metal sulfides, and lithium-containing composite metal oxides between lithium and transition metals. Examples of the transition metals that can be used include Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo. Examples of the transition metal oxides include MnO, MnO 2 , V 2 O 5 , V 6 O 13 , TiO 2 , Cu 2 V 2 O 3 , amorphous V 2 OP 2 O 5 , MoO 3 , V 2 O 5 , V 6 O 13 etc.
[0045] Transition metal sulfides include TiS 2 , TiS 3 , amorphous MoS 2, FeS, etc. Examples of the lithium-containing composite metal oxide include a lithium-containing metal oxide having a layered structure, a lithium-containing composite metal oxide having a spinel structure, a lithium-containing composite metal oxide having an olivine structure, and the like.
[0046] Examples of the lithium-containing composite metal oxide having a layered structure include lithium-containing cobalt oxide (LiCoO 2 ), lithium-containing nickel oxide (LiNiO 2 ), Co-Ni-Mn-based lithium composite oxide, Ni-Mn-Al-based lithium composite oxide, Ni-Co-Al-based lithium composite oxide, LiMaO 2 and a solid solution of Li 2 MbO 3 , xLiMaO 2 ·(1-x)Li 2 MbO 3 (where 0 < x < 1, Ma is one or more transition metals with an average oxidation state of 3 + , and Mb is one or more transition metals with an average oxidation state of 4 + ), and the like.
[0047] Examples of the lithium-containing composite metal oxide having a spinel structure include Li 2 O 4 in which a part of Mn of lithium manganate (LiMn a [Mn 2-x Md x O 4 (where Md is one or more transition metals with an average oxidation number of 4 + , Md = Ni, Co, Fe, Cu, Cr, etc., 0 < x < 1, 0 ≦ a ≦ 1), and the like.
[0048] Examples of the lithium-containing composite metal oxide having an olivine structure include Li y McPO 4 (where Mc is one or more transition metals with an average oxidation number of 3 + , Mc = Mn, Co, etc., 0 ≦ y ≦ 2), and olivine-type lithium phosphate compounds represented thereby, and the like.
[0049] For the negative electrode, carbon-based anodes can be selected, such as graphite, silicon / graphite composites, mesocarbon microbeads (MCMB), hard carbon, soft carbon, alloy-based compounds, intercalation-based compounds, etc. For the cathodes for sodium-ion batteries, layered metal oxides, polyanion compounds, mixed polyanion compounds, and Prussian blue analogues can be selected.
[0050] The particle size of the electrode active material used in the present invention can be appropriately selected according to other battery requirements. For example, the average particle size may be in the range of 0.01 to 50 μm. Similarly, the BET specific surface area of the electrode active material is 0.1 m 2 / g~1000m 2 / g. Here, the "BET specific surface area" refers to the BET specific surface area measured by a nitrogen adsorption method.
[0051] In one embodiment, the electrode active material is present in the slurry in an amount ranging from 60% to 95% by weight, or 65% to 95% by weight, or 65% to 90% by weight, in another embodiment, the amount ranges from 70% to 90% by weight, or 70% to 85% by weight, or 75% to 85% by weight.
[0052] Thus, in one embodiment, the electrode slurry comprises (a) 70% to 85% by weight of electrode active material, (b) 0% to 20% by weight of conductive carbon, and (c) 1% to 20% by weight of plasticizing binder.
[0053] In yet another embodiment, the electrode slurry includes conductive carbon (or electrically conductive carbon). Suitable examples of conductive carbon include carbon black, Super P, acetylene black, ketjen black, reduced graphene oxide, carbon nanotubes, and graphene.
[0054] In one embodiment, the conductive carbon is present in the electrode slurry in an amount ranging from 0% to 20% by weight. In other words, the presence of conductive carbon in the slurry is optional and depends on the type of battery. When present, the amount of conductive carbon ranges from 1% to 20% by weight, or from 2% to 18% by weight, or from 2% to 15% by weight. In another embodiment, the conductive carbon is present in an amount ranging from 5% to 15% by weight, or from 5% to 12% by weight, or from 7% to 12% by weight.
[0055] Thus, in one embodiment, the electrode slurry comprises (a) 65% to 94% by weight of electrode active material, (b) 5% to 15% by weight of conductive carbon, and (c) 1% to 20% by weight of plasticizing binder.
[0056] In yet another embodiment, the electrode slurry includes a plasticizing binder, where the plasticizing binder includes polyvinylidene fluoride (PVDF) and a plasticizer. The PVDF acts as a binder and binds the electrode active materials together. PVDF is widely used as a binder in electrode fabrication to overcome the difficulty of dissolving it in organic electrolytes. Surprisingly, the present invention has observed that plasticizing the binder further improves the electrochemical properties, especially the rate capability and cyclability of the electrode.
[0057] In one embodiment, the molecular weight (M w ) is 5 × 10 3 g / mol~1.1×10 6 In another embodiment, the molecular weight (M w ) is 2 × 10 4 g / mol~1.1×10 6 g / mol, or 5 × 10 4 g / mol~1.1×10 6 g / mol, or 8 × 10 4 g / mol~1.1×10 6 g / mol, or 1 × 10 5 g / mol~1.1×10 6 g / mol, or 5 × 105 g / mol~1.1×10 6 g / mol, or 8 × 10 5 g / mol~1.1×10 6 The range is g / mol.
[0058] Suitable plasticizers may be selected from the group consisting of tetraglyme, diglyme, triglyme, and monoglyme. Glyme, also known as glycol diether, is a saturated acyclic polyether containing no other functional groups. Herein, tetraglyme may be referred to as tetraethylene glycol dimethyl ether, diglyme may be referred to as diethylene glycol dimethyl ether, triglyme may be referred to as triethylene glycol dimethyl ether, and monoglyme may be referred to as ethylene glycol dimethyl ether.
[0059] In one embodiment, the binder is first plasticized before being added to the electrode slurry, for example, a plasticizer can be mixed with a PVDF binder to obtain a plasticized binder.
[0060] In one embodiment, the plasticizer is present in an amount of 1% to 50% by weight based on the weight of PVDF. In another embodiment, the amount ranges from 5% to 50% by weight, or 5% to 45% by weight, or 10% to 40% by weight based on the weight of PVDF. In yet another embodiment, the amount ranges from 10% to 30% by weight, or 15% to 25% by weight based on the weight of PVDF.
[0061] The plasticizing binder is present in the electrode slurry in an amount ranging from 1% to 20% by weight, or from 2% to 18% by weight, or from 2% to 15% by weight, in another embodiment, it is present in an amount ranging from 5% to 15% by weight, or from 5% to 12% by weight, or from 7% to 12% by weight.
[0062] Thus, in one embodiment, the electrode slurry comprises (a) 65% to 95% by weight of electrode active material, (b) 0% to 20% by weight of conductive carbon, and (c) 5% to 15% by weight of plasticizing binder.
[0063] In yet another embodiment, the electrode slurry comprises (a) 70% to 85% by weight of an electrode active material, (b) 5% to 15% by weight of a conductive carbon, and (c) 5% to 15% by weight of a plasticizing binder.
[0064] In another embodiment, the slurry may also include a solvent. Suitable examples of solvents include, but are not limited to, N-methyl-2-pyrrolidone (NMP), acetone, ethanol, dimethylformamide (DMF), dimethylsulfoxide (DMSO), dimethylacetamide (DMAc), water, and mixtures thereof. In one embodiment, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylsulfoxide (DMSO), dimethylacetamide (DMAc), and mixtures thereof.
[0065] Another aspect of the invention relates to a method for preparing the electrode slurries described herein, therefore the embodiments discussed above with respect to the electrode slurries are also applicable here.
[0066] In one embodiment, the method includes mixing the electrode active material, the conductive carbon, and the plasticizing binder in the presence of a solvent. Suitable mixing means here are known to those skilled in the art. For example, a stirrer, a slurry vacuum mixer, or a homogenizer can be used to mix the components. In addition, suitable surfactants and other additives commonly used in the preparation of electrode materials are also known to those skilled in the art and therefore can be used in the present invention. Therefore, the present invention is not limited thereto.
[0067] Yet another aspect of the invention relates to a method for preparing an electrode.
[0068] In one embodiment, the method includes coating an electrode slurry onto a current collector, as described above, and therefore the embodiments described above with respect to the electrode slurry are also applicable here.
[0069] The electrode slurry can be applied to the current collector by a commonly known method without any particular limitation. Specific examples of the application method that can be used include, but are not limited to, a doctor blade method, a dip coating method, a reverse roll coating method, a direct roll coating method, a gravure coating method, an extrusion coating method, and a brush coating method. The slurry can be applied to one or both sides of the current collector. After application, the thickness of the slurry coating on the current collector before drying can be appropriately set according to the thickness of the electrode mixture layer obtained after drying.
[0070] The current collector to which the slurry is applied is a material having good electrical conductivity and electrochemical durability. Specifically, the current collector may be made of, for example, iron, copper, aluminum, nickel, nickel mesh, nickel foam, stainless steel, titanium, tantalum, carbon paper, carbon cloth, graphite, gold, or platinum. Among these materials, copper foil is particularly preferred as the negative electrode current collector. On the other hand, aluminum foil is particularly preferred as the positive electrode current collector. The above materials may be used alone or in combination of two or more in any ratio.
[0071] In the present disclosure, the slurry is applied to the surface of the current collector. In one embodiment, the slurry can coat the surface of the current collector to a suitable thickness, for example, in the range of 10 μm to 1000 μm. Those skilled in the art will recognize suitable coating thicknesses, and the present invention is not limited thereby.
[0072] After the slurry is applied onto the current collector, the drying is not particularly limited and can be performed by a known method. Examples of drying methods that can be used include, but are not limited to, drying with hot air, high-temperature air, or low-humidity air, vacuum drying, and drying by irradiation with infrared rays, electron beams, etc. The drying temperature is preferably 50°C to 200°C. By drying the slurry on the current collector as described above, an electrode mixture layer is formed on the current collector, and a secondary battery electrode including the current collector and the electrode mixture layer is obtained.
[0073] After the drying step, the electrode mixture layer may be further subjected to a pressing step such as mold pressing or roll pressing. The pressing step can improve the adhesion between the electrode mixture layer and the current collector.
[0074] Yet another aspect of the invention relates to an electrode obtained by the method described above, so that the embodiments described above with respect to the method for producing the electrode are also applicable here.
[0075] Yet another aspect of the present invention relates to a battery.
[0076] In one embodiment, the battery comprises the electrodes described above, and therefore the embodiments relating to the electrodes and methods for preparing the electrodes are also applicable here.
[0077] Suitable examples of batteries include lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, aluminum ion batteries, calcium ion batteries, fluorine ion batteries, aqueous batteries, and primary batteries. Batteries may include other components such as separators, electrolytes, etc.
[0078] In the present disclosure, the electrolyte can include a liquid electrolyte, a gel polymer, a solid electrolyte, or a combination thereof. The liquid electrolyte can include a lithium or sodium salt, an organic solvent, or a combination thereof, and the gel electrolyte can include, but is not limited to, an organic solid electrolyte including a polymer compound, an inorganic solid electrolyte, or a combination thereof. The solid electrolyte can include an organic solid electrolyte including a polymer compound, an inorganic solid electrolyte, or a combination thereof.
[0079] In the present disclosure, when the electrolyte is a liquid electrolyte, it includes an electrolyte salt and a solvent. The electrolyte salt used in the present invention includes sodium-containing hydroxides (e.g., sodium hydroxide (NaOH) and the like), borates (e.g., sodium metaborate (NaBO 2 ), Borax (Na 2 B 4 O 7 ), boric acid (H 3 BO 3 ), phosphates (e.g., trisodium phosphate (Na 3 PO 4 ), Sodium pyrophosphate (Na 2 HPO 4 ) etc.), chloric acid (e.g., NaClO 4 etc.), NaAlCl 4 , NaAsF 6 , NaBF 4 , NaPF 6 , NaSbF 6 , NaCF 3 SO 3 , NaN(SO 2 CF 3 ) 2 , NaFSI, NaTFSI, sodium fluoride, sodium sulfate, sodium nitrate, and sodium lignosulfonate. 6 , LiFSI, LiTFSI, LiCF 3 SO 3 , and LiClO 4 Lithium salts such as, but not limited to, can also be used.
[0080] In the present disclosure, the solvent can be any medium through which ions involved in the electrochemical reaction of the battery can move, without any particular limitations. Specifically, the solvent may be an aqueous solvent such as water or alcohol, or a non-aqueous solvent such as an ester solvent, an ether solvent, a ketone solvent, an aromatic hydrocarbon solvent, an alkoxyalkane solvent, or a carbonate solvent. One solvent selected from these solvents or a mixture of two or more solvents may be used.
[0081] Suitable solvents may be selected from the group consisting of trimethyl phosphate (TMP), triethyl phosphate (TEP), methyl ethyl carbonate, methyl propionate carbonate, ethyl propionate, ethyl acetate, ethyl methyl carbonate, methyl formate, propylene carbonate, ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, methyl acetate, triethylene glycol dimethyl ether, dimethyl sulfone, dimethyl ether, ethylene sulfite, diethyl carbonate, dimethyl carbonate, propylene oxide, propylene sulfite, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propyl acetate, methyl butanone, methyl isobutyl ketone, toluene cyclohexanone, ethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0082] Here, the separator separates the negative electrode and the positive electrode from each other and provides a path for the movement of metal ions, and any known separator can be used for this purpose. In other words, a separator that has excellent moisture retention for the electrolyte and low resistance to the movement of electrolyte ions can be used. For example, the separator can be selected from glass microfiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. Preferably, a polyolefin-based polymer separator such as polyethylene or polypropylene is used in the metal ion secondary battery, and a coated separator containing a ceramic component or a polymer material may be used to ensure heat resistance and mechanical strength. If necessary, the separator may have a single-layer structure or a multi-layer structure.
[0083] Yet another aspect of the present invention relates to an electrolysis device.
[0084] In one embodiment, the electrolysis device comprises the electrodes described above, and therefore the embodiments relating to the electrodes and methods for preparing the electrodes are also applicable here.
[0085] Yet another embodiment of the present invention relates to a fuel cell.
[0086] In one embodiment, a fuel cell comprises the electrodes described above, and therefore the embodiments relating to the electrodes and methods for preparing the electrodes are also applicable here.
[0087] Advantageously, the present invention provides an improved electrode slurry for producing electrodes. The resulting electrodes have acceptable and improved electrochemical performance in terms of rate capability and cyclability. Furthermore, the present invention also provides for easy production of electrodes with optimal processing conditions.
[0088] While the foregoing description discloses various embodiments of the present disclosure, other and further embodiments of the present invention may be devised without departing from the basic scope of the present disclosure. The present invention is not limited to the described embodiments, variations, or examples, which, in combination with the information and knowledge available to those skilled in the art, are included to enable one of ordinary skill in the art to make and use the invention. EXAMPLES
[0089] The presently claimed invention is illustrated by the following non-limiting examples.
[0090] Compound: Active material LiFePO 4 / LiNi 0.5 Mn 0.3 Co 0.2 O 2 / Graphite / Hard Carbon / Na 3 (VOPO 4 ) 2 F Binder: Polyvinylidene fluoride (PVDF) Plasticizers: Tetraglyme, triglyme, diglyme, monoglyme Conductive Carbon Super P Solvent: N-methyl-2-pyrrolidone (NMP) Electrode slurries were prepared by mixing 80 wt% active material, 10 wt% conductive carbon, 10 wt% PVDF, and an appropriate amount of NMP to obtain a homogeneous mixture. 5 wt% to 50 wt% plasticizer was added to this mixture to obtain a viscous slurry. The slurries were then applied to Al / Cu foils by doctor blade method and dried in a vacuum oven at 120 °C to obtain electrodes with various plasticizers. The electrodes were then calendered and punched to a diameter size of 15 mm. 1M LiPF in ethylene carbonate / diethyl carbonate with Li / Na as counter / reference, polypropylene / glass microfiber as separator, and 5% fluoroethylene carbonate as electrolyte. 6or 1M NaClO in propylene carbonate containing 5% fluoroethylene carbonate 4 A half cell was fabricated using the above.
[0091] Details of the various electrodes are given in Table 1 below.
[0092] [Table 1]
[0093] Figure 1(a) shows LiFePO cycled at 0.1C. 4 The graph shows the constant current charge / discharge curves of LiFePO prepared using a plasticizer. 4 The LiFePO electrode (LFP-P) shows a better charge-discharge profile than the electrode without plasticizer (LFP). Figure 1(b) shows the LiFePO electrode prepared with plasticizer. 4 The graph shows the rate capacity where the electrode performed better than the other electrodes. For example, at 10C, the capacity of the electrode with plasticizer was about 95mAh / g, while the capacity of the electrode without plasticizer was 10mAh / g.
[0094] Figure 2(a) shows the galvanostatic charge-discharge curves of graphite cycled at 0.1C. The graphite anode prepared with plasticizer (graphite-P) shows a better charge-discharge profile than the anode without plasticizer (graphite). The reversible capacity obtained at the second cycle was 400 mAh / g for graphite-P and 320 mAh / g for the one without plasticizer (graphite). Figure 2(b) shows the rate capacity graph where the graphite-P electrode prepared with plasticizer performed better than the one without plasticizer. For example, at 1C, the capacity of the electrode with plasticizer was about 350 mAh / g, while the capacity of the other electrode (without plasticizer) was 250 mAh / g. Figure 2(c) shows the cycle performance where graphite-P was found to have a higher capacity and better capacity retention than the one without plasticizer.
[0095] Figure 3(a) shows the galvanostatic charge-discharge curves of NMC cycled at 0.1C. The NMC cathode prepared with plasticizer (NMC-P) shows a similar capacity to the cathode without plasticizer (NMC), but the rate performance is significantly improved over the non-plasticized cathode. Figure 3(b) shows the rate performance graph of the NMC-P electrode prepared with plasticizer. Again, the NMC-P electrode with plasticizer showed better performance than the electrode without plasticizer. For example, at 1C, the capacity of the electrode with plasticizer was about 140 mAh / g, while the capacity of the electrode without plasticizer was less than 100 mAh / g. Figure 3(c) shows the cycling performance of the NMC-P electrode at 1C rate for 250 cycles.
[0096] Figure 4(a) represents the first two galvanostatic charge-discharge curves of the hard carbon anode cycled at 0.1C. The graphite anode prepared with plasticizer (hard carbon-P) shows better capacity than the anode without plasticizer (hard carbon). The reversible capacity obtained at the second cycle was 280 mAh / g for hard carbon-P and 280 mAh / g for the one without plasticizer (hard carbon). Figure 4(b) shows the rate capacity graph where the hard carbon-P-TG electrode prepared with plasticizer (tetraglyme) performed better than the other electrodes. For example, at 1C, the capacity of the electrode with plasticizer was about 260 mAh / g, while the capacity of the electrode without plasticizer was only 180 mAh / g. Figure 4(c) shows the rate capacity graph where the hard carbon-P-DG electrode prepared with plasticizer (diglyme) performed better than the other electrodes. For example, at 1C, the capacity of the electrode with plasticizer was about 260 mAh / g, while the capacity of the electrode without plasticizer was 180 mAh / g. Figure 4(d) shows the cycling performance of hard carbon-P tested at 2C rate for over 2500 cycles. Even after 2500 cycles, the capacity retention was 80%.
[0097] Figure 5(a) shows the results of Na cycled at 0.1C. 3 (VOPO 4 )2 Figure 5 shows the galvanostatic charge-discharge curves of F (NVOPF-P and NVOPF). As can be seen from Figure 5(a–c), the samples containing plasticizer have better capacity, rate capability, and cyclability than the samples without plasticizer.
[0098] From the above, it can be concluded that the electrode slurry of the present invention improves the electrochemical properties of the electrode.
Claims
1. 60% to 98% by weight of an electrode active material; 0% to 20% by weight of conductive carbon, and 1% to 20% by weight of a plasticizing binder wherein the weight percentage is based on the total weight of the slurry; An electrode slurry, wherein the plasticizing binder comprises polyvinylidene fluoride and a plasticizer selected from the group consisting of tetraglyme, diglyme, triglyme, and monoglyme.
2. 2. The electrode slurry of claim 1, wherein the plasticizer is present in an amount ranging from 1% to 50% by weight based on the weight of the polyvinylidene fluoride.
3. 3. The electrode slurry according to claim 1 or 2, wherein the plasticizing binder is obtained by mixing polyvinylidene fluoride with a plasticizer.
4. A method for preparing the electrode slurry according to any one of claims 1 to 3, comprising mixing an electrode active material, a conductive carbon, and a plasticizing binder in the presence of a solvent to obtain an electrode slurry.
5. 5. The method of claim 4, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylsulfoxide (DMSO), and dimethylacetamide (DMAc).
6. A method for preparing an electrode by applying the electrode slurry of claim 1 or the electrode slurry obtained from the method of claim 4 or 5 onto a current collector.
7. The method of claim 6, wherein the current collector is dried at a temperature in the range of 50°C to 200°C.
8. 8. An electrode obtainable by the method according to claim 6 or 7.
9. A battery comprising the electrode of claim 8.
10. 9. The battery of claim 8, wherein the battery is selected from lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, aluminum ion batteries, calcium ion batteries, fluorine ion batteries, aqueous batteries, and primary batteries.
11. Electrolytic device comprising an electrode according to claim 8 or an electrode obtained from the method according to claim 6 or 7.
12. A fuel cell comprising an electrode according to claim 8 or an electrode obtained from the method according to claim 6 or 7.
